Palestina al Sur - Osorio, Daniel (Antipoder, 2011)
After the fall of Saddam Hussein, thousands of Palestinians became refugees in no man's land. The distant Republic of Chile welcomed a group of them to live in the small city of La Calera, as it did over 100 years ago with Palestinian immigrants escaping Ottoman oppression. Today, like a century ago, the journey repeats itself ... Basem, a young Palestinan who arrived with his wife and young daughter, faces his new country full of enthusiasm, ingenuousness and hope, longing for a place to call home in an unknown, seductive and contradictory world, thousand of kilometers from his homeland. In his new country, Basem recovers his trade as baker and sets up his own business. He hopes his efforts, together with the help of the big community of Palestinian descendants, will lead him to accomplish his dream: to bring his elderly parents, still trapped at the refugee camp, to live with him again, now in Chile.